2022
DOI: 10.3390/jpm12030372
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health among Elderly, Impact on Life Quality, Access of Elderly Patients to Oral Health Services and Methods to Improve Oral Health: A Narrative Review

Abstract: Dental health is often neglected among the elderly because of the numerous comorbidities in this population, such as cardiovascular diseases. However, dental health influences general health and quality of life by impacting both the general health and the psychological state of the individual. The present review highlights the main dental comorbidities in the elderly population, their impact on the quality of life, the barriers towards access to dental care in the elderly and methods to improve their dental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 107 publications
3
39
0
4
Order By: Relevance
“…Therefore, as we hypothesized, there is a relation between the neglect of oral health, on the one hand, and distrust in dental services, on the other hand, reduced psycho-social functioning caused by poor oral health and lack of care for one's own oral health. This result corroborates those studies which demonstrated that individuals who neglect their oral cavity have a low quality of life [4,5,15,23,46], are less oriented towards dental services [5,23], and they do not give any importance to oral health [20,47].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, as we hypothesized, there is a relation between the neglect of oral health, on the one hand, and distrust in dental services, on the other hand, reduced psycho-social functioning caused by poor oral health and lack of care for one's own oral health. This result corroborates those studies which demonstrated that individuals who neglect their oral cavity have a low quality of life [4,5,15,23,46], are less oriented towards dental services [5,23], and they do not give any importance to oral health [20,47].…”
Section: Discussionsupporting
confidence: 91%
“…According to the World Oral Health Report 2003, oral diseases are age-related, with most oral diseases sharing risk factors with chronic diseases, and oral health is an important component of overall health and quality of life (QOL) [5]. However, when discussing health issues among the elderly, oral health is frequently overlooked [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A high amount of tooth loss, dental caries, periodontal diseases, dry mouth, and the chance of developing oral precancer/cancer were the most evident signs of poor oral health in the elderly [6,8,9]. The link between oral health and overall health is especially 2 of 13 pronounced in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it could also affect a person's appearance, self-esteem, psychosocial functioning, and quality of life. Studies have shown that oral diseases could cause psychological burdens [ 27 ]. The quality of life in this age group is critical.…”
Section: Introductionmentioning
confidence: 99%